Petrographic and Geochemical Investigations on the Pottery Production from Arslantepe–Malatya (Eastern Anatolia) from the Fourth to the Second Millennium BCE: Technological Continuity, Innovation and Cultural Change. (5th January 2017) - Fragnoli, P.; Palmieri, A. M.
Abstract : The petrographic and geochemical analyses of 130 Late Chalcolithic 3 (LC3, 3800bce ) to Early Bronze Age IIIB (EBAIIIB, 2000bce ) ceramics from Arslantepe and the Malatya Plain in the Eastern Anatolian Upper Euphrates have identified critical differences in raw material procurement and paste preparation, reflecting typological, chronological and cultural changes. Based on these differences, distinct modes of production that correspond to phases reflecting significant social, economic and political changes were recognized. In particular, the interruption of the centralization process and the establishment of mobile groups during EBAI (3000–2900bce ) were accompanied by the exploitation of new sources.